Поверхневі явища у двовимірних структурах макропористого кремнію - Ivanov, V. I.; Karachevtseva, L. A.; Lytvynenko, O. A.; Parshyn, K. A.; Stronska, O. J. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2009)
The results of researches of photophysical processes in 2D macroporous silicon structures are presented. We have studied photoconductivity and absorption of these structures in near infrared range which define fimctionalities of the materials.